Future Foods 2017
DOI: 10.5772/intechopen.70271
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Evaluation of Earthworms as Human Food

Abstract: Earthworms have been a traditional medicine in China for at least 2300 years. Because of medicine food homology in China, people have been using earthworms as a food for several centuries. Earthworms are rich in protein and various amino acids; the protein content of earthworm meal was 54.6-59.4% on dry weight. Their protein content and amino acid composition are beter than those of ish meal, cow milk and soybean meal. The crude fat content of earthworm meal was 7.34%. Earthworm protein is easily hydrolyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…Then, the earthworm meal was defatted to obtain a meal rich in protein and other nutrients and to decrease perishability. The results showed that earthworm grown on FVW presented a high protein content, from 62.3% on DM before the defatting process to about 73% on DM in the sterilized defatted sample, similar to percentages reported in other studies [14,[16][17][18][19][20]. Moreover, iron and iodine minerals are also well represented.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Then, the earthworm meal was defatted to obtain a meal rich in protein and other nutrients and to decrease perishability. The results showed that earthworm grown on FVW presented a high protein content, from 62.3% on DM before the defatting process to about 73% on DM in the sterilized defatted sample, similar to percentages reported in other studies [14,[16][17][18][19][20]. Moreover, iron and iodine minerals are also well represented.…”
Section: Discussionsupporting
confidence: 85%
“…Several authors [14,15] have underlined the nutritional value of earthworms based on their nutrient content: earthworms of Eisenia foetida species are an excellent source of biologically valuable protein, micronutrients, minerals, and vitamins in the human diet. E. foetida meal has a high protein content in the range of 54.6% to 71% dry matter [14,[16][17][18][19][20] and is rich in amino acids considered essential for humans [17]. Earthworms are also rich in fat, with content ranging from 7.3% to 10% of dry matter [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, P'ing-Chou k'o-t'an, a special dish from Hainan Island, is earthworm cooked with pieces of bamboo. Nowadays, some people in Fujian, Guangdong, and Taiwan still consume earthworm in their diet [6]. In Japan, making earthworm pie has been recorded as a custom [7].…”
Section: Earthworm As a Delicacymentioning
confidence: 99%
“…In China, not only was earthworm listed in well-known ancient medicinal books, such as Shennong Ben Cao Jing or Ben Cao Gang Mu, it was also covered and described in contemporary publications like Pharmacopoeia of People's Republic of China [6,29]. A clinical study showed that gyanyankan (a Chinese medicine mixture including earthworms) was effective in treating patients' mild hypertension [30,31].…”
Section: Traditional Medicinementioning
confidence: 99%